2006
DOI: 10.17305/bjbms.2006.3177
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low Back Pain in Individuals with Lower-limb Amputation

Abstract: Low back pain (LBP) is a common condition in individuals which experienced psychology and physical trauma. LBP is usually found in persons with lower-limb amputation (LLA), as the most common sign of somatisation or inappropriately made prostheses. Our goal was to investigate cases of chronic pain syndrome in persons with LLA and to determine factors, which influence their functional inability due to LBP. Pain after LLA has been studied. 37 persons, including 26 war veterans (70.2 %) and 11 (29.8 %) civilians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…Back pain has, however, been shown to occur frequently among lower extremity amputees, and has been reported as persistent and chronic by 52–72% of participants with different levels of amputation caused either by trauma or other illnesses (tumour/dysvascular). 8,15 In yet another study, prevalence of low back pain among transfemoral amputees was frequent to permanent in 26.3% of the sample. 16…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Back pain has, however, been shown to occur frequently among lower extremity amputees, and has been reported as persistent and chronic by 52–72% of participants with different levels of amputation caused either by trauma or other illnesses (tumour/dysvascular). 8,15 In yet another study, prevalence of low back pain among transfemoral amputees was frequent to permanent in 26.3% of the sample. 16…”
Section: Introductionmentioning
confidence: 91%
“…6 The use of an increased pelvic tilt and Trendelenburg gait to maintain knee stability and reduce the lever arm of the hip abductors 7 often leads to back pain. 8 Transtibial amputees have better biomechanical prerequisites compared to transfemoral and knee disarticulation amputees. 6,9,10 There is evidence that distal and unilateral amputees have better walking ability 11 and walk faster 12 than transfemoral amputees.…”
Section: Introductionmentioning
confidence: 99%
“…In vielen der Literaturstellen werden mehrere Veränderungen mehr oder weniger detailliert bearbeitet. 17 Literaturstellen berichten über Rückenschmerzen bei Amputierten [3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]…”
Section: Identifizierte Literaturunclassified
“…In der Mehrzahl der Studien wurden Kriegsversehrte untersucht [9,10,15,17,28], aber auch andere Amputationsursachen wie nicht kriegsbedingte Traumata, Tumoren, Durchblutungsstörungen oder angeborene Fehlbildungen sind in den analysierten Studien [ Um eine grobe Abschätzung der Prävalenz von Veränderungen am Bewegungsapparat als Folge einer Amputation an der unteren Extremität vornehmen zu können, wurden die quantitativen Ergebnisse aus verschiedenen Studien zusammengefasst. Ziel war es dabei, eine möglichst große und damit auch repräsentative Datenmenge zu erhalten.…”
Section: Diskussionunclassified
“…Furthermore, 67% of persons experienced pain in one area, 28% in two areas, and 5% in three areas. The other included studies predominantly reported low back pain [4][5][6]8,12,13,22,24,27,29,33,[37][38][39]41,[44][45][46][47][48][49][50][51][52]60,62]. Several studies reported data about the experienced pain frequency [6,8,27,45,47,49].…”
Section: Back Painmentioning
confidence: 99%